EXAMINATION OF FIGURATIVE LANGUAGE VARIETY AND DENSITY IN THE SONG “NIGHTMARES NEVER END” - Simanjuntak, Kezia Grace Rejoicelyn; Jayantini, I Gusti Agung Sri Rwa (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Figurative language is an important device in literature, specifically in trying to enrich meaning and emotional on creative expression, and especially in song lyrics. While its presence in popular music is widely known, a detailed and comprehensive analysis focused on the density, variety, and interplay of the ten figurative language types within a single song has not been commonly explored. The purpose of this study is to identify and analyse the density and variety, as well as the functions of ten figurative language types classified by Knickerbocker and Reninger, within the song lyrics of JT Music’s “Nightmares Never End.” This study also looks into lexical density, and how richness in vocabulary correlates to figurative language’s density. With a qualitative content analysis approach, the lyrics were analysed and categorised accordingly. The analysis successfully analysed ten types of the figurative language, resulting in a total of 27 instances found in the lyrics. This density and varied types show the song’s richness in linguistic artistry and metaphorical meanings, contributing to its theme of psychological issues, struggles, and loneliness. These findings highlight the intricate use of figurative language, showing the interplay between the types that enhance the song’s thematic depth expressed through the words used.